Key criteria for the ethical acceptability of COVID-19 human challenge studies: Report of a WHO Working Group. Issue 4 (22nd January 2021) - Jamrozik, Euzebiusz; Littler, Katherine; Bull, Susan; Emerson, Claudia; Kang, Gagandeep; Kapulu, Melissa; Rey, Elena; Saenz, Carla; Shah, Seema; Smith, Peter G; Upshur, Ross; Weijer, Charles; et al.
Abstract: This report of the WHO Working Group for Guidance on Human Challenge Studies in COVID-19 outlines ethical standards for COVID-19 challenge studies. It includes eight Key Criteria related to scientific justification, risk-benefit assessment, consultation and engagement, co-ordination of research, site selection, participant selection, expert review, and informed consent. The document aims to provide comprehensive guidance to scientists, research ethics committees, funders, policymakers, and regulators in deliberations regarding SARS-CoV-2 challenge studies by outlining criteria that would need to be satisfied in order for such studies to be ethically acceptable.